The Zero Power Rule states that any non-zero number raised to the power of zero is equal to 1. Therefore:
-
For \((-33)^0\), we have: \[ (-33)^0 = 1 \]
-
For \(27^0\), similarly: \[ 27^0 = 1 \]
Now, let's apply this to simplify the original expression:
\[ 9 \cdot (-33)^0 + \frac{3}{2}(8 - 27^0) \]
Substituting in the values we've calculated:
\[ 9 \cdot 1 + \frac{3}{2}(8 - 1) \]
This simplifies to:
\[ 9 + \frac{3}{2}(7) \]
Now, calculating \(\frac{3}{2}(7)\):
\[ \frac{3 \cdot 7}{2} = \frac{21}{2} \]
Putting everything together gives us:
\[ 9 + \frac{21}{2} \]
Now, to express \(9\) in terms of halves, we can write it as:
\[ \frac{18}{2} \]
Thus we have:
\[ \frac{18}{2} + \frac{21}{2} = \frac{39}{2} \]
In the format requested, we can break it down in the following way:
\[ 9 \cdot (1) + \frac{3}{2}(8 - 1) \]
Which can be filled in as:
\[ 9 \cdot 1 + \frac{3}{2}(8 - 1) \]
Thus, the equivalent expression with the blanks filled is:
\[ 9 \cdot 1 + \frac{3}{2}(8 - 1) \]
So the filled blanks are:
\[ \text{blank} = 9, \text{blank} = 1, \text{blank} = 8, \text{blank} = 1 \]